Os jogos no processo de alfabetização e letramento - Costa, Márcia Aparecida da Silva (2021)
The concepts of literacy and lettering have expanded in recent decades to account for the process that involves teaching/learning to read and write in contemporary times. Thus, it is assumed that gamification and educational games can enhance reading and writing education. It is believed that gamification and educational games can encourage students to participate with greater engagement in the proposed activities. In this context, the present research has as primary objective of investigating the contribution of games in the consolidation of students' language skills in two classes of the 2nd year of Elementary School and for the work of literacy teachers from a municipal school in the south of Minas Gerais. This investigation established as specific objectives: (i) analyzing the use of games by literacy teachers as a teaching methodology and (ii) applying activities on language literacy skills by using games with 2nd-year students of Elementary School I. The theoretical framework was built using authors such as Alves, Minho, and Diniz (2014), Busarelo, Ulbricht, and Fadel (2014), Colello (2004), Freire (2005), Gil (2002), Grando (2012), Huizinga (1999), Kishimoto (2010), Kleiman (2007, 2014), Ludke and André (1986), Maciel and Lúcio (2008), Soares (2002, 2016), Viana et al. (2013), and Zichermann and Cunningham (2011). The data regarding the application of games were recorded in a logbook, analyzed in the light of the theoretical framework, obtaining the data in the participatory research. Thus, the research demonstrated that games could enhance teaching and contribute to the consolidation of language skills as a diagnostic assessment methodology since the teacher can map the skills students master and what they still need to work through the game. The research has shown that games contribute significantly to the work of literacy teachers.